Dichotic listening versus dichhaptic braille reading - Kumar PJ (Journal of All India Institute of Speech and Hearing, 1970)
Ten congenitally totally blind male adults were administered Dichhaptic Braille Reading and Dichotic Listening Tasks. The performance of the hands on Dichhaptic Braille Reading were compared with the performances of the ears on Dichotic Listening. The study was to examine the hemispheric specialization for spatial linguistic stimuli, such as Braille. Nine of the ten subjects s,howed an RHA and an REA on tasks involving simultaneous reception of stimuli by the right and the left. This suggested a left he-misphere specialization both for spatial linguistic and auditory linguistic meaningful stimuli.